2022
DOI: 10.3389/fruro.2022.969208
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal laser ablation of the prostate with EchoLaser™ system: perioperative and short-term functional and sexual outcomes

Abstract: ObjectiveTo date, several ultra-minimally-invasive surgical techniques are available for the treatment of male LUTS due to benign prostatic obstruction (BPO). Herein we report our preliminary experience with SoracteLite™ TPLA for the treatment of carefully selected patients with LUTS due to BPO.MethodsData from all consecutive patients undergoing TPLA at our institution between April 2021 and February 2022 were prospectively collected in a specific database. Data regarding functional and sexual outcomes evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…15 Similarly, all patients retained erectile function and ejaculation in the study by Manenti et al, 17 with a mean score of ejaculatory function, as assessed by the Male Sexual Questionnaire -Erectile Dysfunction (MSHQ-EiD) questionnaire, showing improvement. Sessa et al 20 reported preserved ejaculation in all patients and improvement in 15-29%, while erections were stable or even showed some improvement (+2-4%). Finally, Bertolo et al 10 in their RCT showed that 96% of patients who underwent TPLA preserved their ejaculation.…”
Section: Sexual Functionmentioning
confidence: 90%
See 4 more Smart Citations
“…15 Similarly, all patients retained erectile function and ejaculation in the study by Manenti et al, 17 with a mean score of ejaculatory function, as assessed by the Male Sexual Questionnaire -Erectile Dysfunction (MSHQ-EiD) questionnaire, showing improvement. Sessa et al 20 reported preserved ejaculation in all patients and improvement in 15-29%, while erections were stable or even showed some improvement (+2-4%). Finally, Bertolo et al 10 in their RCT showed that 96% of patients who underwent TPLA preserved their ejaculation.…”
Section: Sexual Functionmentioning
confidence: 90%
“…After excluding 74 records (65 due to irrelevant subjects, 3 conference abstracts, and 6 protocols with no published outcomes), 25 full texts were screened for eligibility. Finally, after excluding 3 reviews and 11 studies not on BPH or transperineal route of therapy, 11 studies were deemed eligible for inclusion: 1 RCT, 10 1 animal study, 11 and 9 observational studies, [12][13][14][15][16][17][18][19][20] from which one was comparative. 12 Since only two comparative studies were found, one of which was an RCT and they compared TPLA with either PAE or TURP, no meta-analysis was performed.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations